2017
DOI: 10.1101/190579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Role Of Circle Of Willis Anatomy Variations In Cardio-embolic Stroke - A Patient-specific Simulation Based Study

Abstract: We describe a patient-specific simulation based investigation on the role of Circle of Willis anatomy in cardioembolic stroke. Our simulation framework consists of medical image-driven modeling of patient anatomy including the Circle, 3D blood flow simulation through patient vasculature, embolus transport modeling using a discrete particle dynamics technique, and a sampling based approach to incorporate parametric variations. A total of 24 (four patients and six Circle anatomies including the complete Circle) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 60 publications
0
11
0
2
Order By: Relevance
“…Being familiar with the most common CoW variations and their prevalence can be of vital importance to clinicians. Many authors have suggested an increased risk of ischemic stroke in the presence of CoW variations (Chuang, Liu, Pan, & Lin, 2008; Hoksbergen et al, 2003; Mukherjee, Jani, Narvid, & Shadden, 2018). Chuang et al (2008), for example, highlight that hypoplasia of the PComA is associated with an increased risk of infarction, particularly in the thalamic region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being familiar with the most common CoW variations and their prevalence can be of vital importance to clinicians. Many authors have suggested an increased risk of ischemic stroke in the presence of CoW variations (Chuang, Liu, Pan, & Lin, 2008; Hoksbergen et al, 2003; Mukherjee, Jani, Narvid, & Shadden, 2018). Chuang et al (2008), for example, highlight that hypoplasia of the PComA is associated with an increased risk of infarction, particularly in the thalamic region.…”
Section: Discussionmentioning
confidence: 99%
“…Mukherjee et al (2018) suggest that variant CoW anatomy can have an impact on the trajectory of microemboli, and hence lead to infarctions in distal, more unusual areas of the brain. Therefore, being aware of variations and their frequency can help us understand atypical stroke patterns, and predict their likelihood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mukherjee et al divided the embolism process into three independent steps, and estimated the risks of embolism from a probabilistic view using FSI simulation (Fig.4a) [75]. They applied the FSI model in 24 cases and concluded that anatomical variations of CoW significantly influenced embolus distribution to the six major cerebral arteries while MCA territory was least sensitive to the influence of anatomical variations [76].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…The ICA supplies oxygenated blood to most midline portions of the frontal lobe and superior medial parietal lobe. It is the most important blood supply of the cerebral circulation from the circle of Willis (5). The MCA receives 80% of the carotid blood flow, whereas the ACA receives 20%.…”
Section: Introductionmentioning
confidence: 99%